ANALISIS PELAKSANAAN FUNGSI MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN ANAK USIA DINI DI PAUD FILADELFIA PATUMBAK II - Juwita Makaria Tambunan; Kamtini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes how the school principal implements the management functions of planning, organizing, actuating, and controlling at PAUD Filadelfia Patumbak II, and identifies the factors that support and inhibit their implementation. Preliminary observation found that learning planning ran below its potential, learning media use remained limited, and supervision and evaluation lacked consistency. Using a qualitative single case study design, the study drew data from one principal as the key informant and four teachers as supporting informants through in-depth interviews, observation, and documentation. Data were analyzed with the interactive model of Miles, Huberman, and Saldaña and validated through source and method triangulation. The four management functions generally ran well, though their effectiveness varied. Six supporting factors spanned internal and external dimensions, while four inhibiting factors emerged: limited facilities and operational funding, the principal's limited digital literacy, disrupted supervision during the principal's maternity leave, and one teacher's academic qualification below the required standard. These findings point to a leadership-substitution protocol, digital literacy training for principals, and accelerated qualification support for underqualified teachers as concrete steps for strengthening management practice in similarly resourced early childhood institutions.